Perancangan User Experience Aplikasi Publikasi Buku Digital menggunakan Metode Five Planes - Joang Pratama Achmad; Komang Candra Brata; Lutfi Fanani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Students spend a lot of money in completing research for graduation to find references. This causes many students did piracy. The development of a digital book publication apps prototype is carried out in order to become an inexpensive solution for students in finding digital books or supporting references. The subscription system is made to be an inexpensive solution to the prototypes being made. The design is carried out by taking into account the aspects of the user experience based on the five-field method consisting of 5 layers, namely strategy plane, scope plane, structure plane, skeleton plane, and surface plane. The [initial interviews were conducted to obtain results that did not require the user to construct. A persona is determined that is used as a reference for creating functional, task flow, and hierarchical task analysis (HTA). HTA is used as a reference for making low-fidelity designs which later created a prototype. The evaluation process uses a task scenario for users and the User Experience Questionnaire (UEQ) as an assessment of user experience that generate attractiveness value of 1,433 with above average level, a perspective value of 1,250 with below average level, an efficiency value of 1,250 with above average level, the value of dependability is 1,500 with good level, a stimulation value of 0.900 with below the average level, and a novelty value of 0.050 with bad level. Evaluation using the System Usability Scale (SUS) method was carried out as a usability measurement that generate value of 78.5 or B+ in letter-grade form.